The diagrams of architecture - Garcia, Mark (AD reader, 2010)
"Diagrams of Architecture is the first anthology to represent - through texts and diagrams - the histories, theories and futures of architecture through the diagram." "Spanning the Pre-historic to the Parametric, Diagrams of Architecture illustrates over 250 diagrams and brings together 26 previously published and newly commissioned essays from leading international academics, architects, theorists and professional experts. These combine to define the past and future of the diagram's discourse. Prefaced with a critical introduction by Mark Garcia, each text investigates a central concept or dimension of the diagram ranging from socio-cultural studies, science, philosophy, technology, CAD/CAM, computing and cyberspace and virtual/digital design to methodology, environment/sustainability and phenomenological, poetic and art architecture; as well as interior, urban, engineering, interactive and landscape design."--BOOK JACKET.